2022
DOI: 10.1007/s10654-021-00818-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term association of pregnancy and maternal brain structure: the Rotterdam Study

Abstract: The peripartum period is the highest risk interval for the onset or exacerbation of psychiatric illness in women’s lives. Notably, pregnancy and childbirth have been associated with short-term structural and functional changes in the maternal human brain. Yet the long-term effects of pregnancy on maternal brain structure remain unknown. We investigated a large population-based cohort to examine the association between parity and brain structure. In total, 2,835 women (mean age 65.2 years; all free from dementi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
5
2
0
Order By: Relevance
“…Here, we discuss the potential for these effects to be driven by a combination of 1) direct/caregiving, 2) indirect/environmental, and/or 3) covarying/sociodemographic mechanisms. While the factors underpinning this neuroprotective effect require further study, these results are consistent with the extant human and animal parental brain literatures, which point to structural [27][28][29][30][31][32][33] and functional 26 neuroprotection in mothers [26][27][28][29][30][31][32][33] and fathers 30 with more children.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Here, we discuss the potential for these effects to be driven by a combination of 1) direct/caregiving, 2) indirect/environmental, and/or 3) covarying/sociodemographic mechanisms. While the factors underpinning this neuroprotective effect require further study, these results are consistent with the extant human and animal parental brain literatures, which point to structural [27][28][29][30][31][32][33] and functional 26 neuroprotection in mothers [26][27][28][29][30][31][32][33] and fathers 30 with more children.…”
Section: Discussionsupporting
confidence: 84%
“…This effect is strong at an individual connection-level, and even stronger at a network-level, and exists for both females and males, suggesting a neuroprotective effect of parenthood on brain function in later life. This finding, though striking, is in line with our hypothesis, as well as the current understanding of the enduring impact of parenthood on the parental brain in humans [27][28][29][30][31][32] and animals [34][35][36] . Indeed, a growing literature examining brain structure in later life parenthood demonstrates 'younger-looking' brains in adults with more children [27][28][29][30][31][32][33] , painting a consistent picture of parity-related protection for the structure of the adult brain.…”
Section: Parity and Age Have Contrasting Effects On Brain Functionsupporting
confidence: 90%
See 2 more Smart Citations
“…30 This is in line with previous studies showing that parity and longer reproductive lifespans are associated with lower rates of silent brain infarcts, 31 strokes, 32 dementia, 33 and brain atrophy. [34][35][36][37] Alternatively, studies have suggested that the rather subtle increase in WMHV associated with normal aging 38 is linked to microglial and endothelial activation, 28,39 indicating that women with high premenopausal LHE may be better protected against age-related inflammation of the brain. 40 This agrees with animal models showing that circulating estrogen can reduce the inflammatory response, which could be dose-dependent.…”
Section: Discussionmentioning
confidence: 99%